Preparation of Zinc Layered Hydroxides-cinnamaldehyde Nanocomposites and its Physico-Chemical Study - Jamaluddin Nurul Jannah, Saidi Nurul Adila, Mohamad Jaafar Adila, (Universiti Pendidikan Sultan Idris, 2017)
Preparation of Zinc Layered Hydroxides-cinnamaldehyde Nanocomposites and its Physico-Chemical Study by Jamaluddin Nurul Jannah, Saidi Nurul Adila, Mohamad Jaafar Adila,